Evolving technologies in regenerative medicine - P. Hollands; T. Tkebuchava (CellR4, 2022)
This short review explores the constantly evolv- ing technology, both cellular and equipment or technology based, which is currently being ex- perienced in the field of regenerative medicine. There is considerable ongoing research into stem cell technologies but there is currently a translational block in bringing some of these technologies to the clinic. We propose new and evolving technologies which may resolve this cell-based block and quickly bring regenerative medicine technologies safely and effectively to patients in need